Uso de agentes bilógicos e fitoquímicos visando ao manejo de Spodoptera eridania (Lepidoptera: Noctuidae) - Damascena, Alixelhe Pacheco (2023)
Olericulture is an excellent option for family farming. However, the cultivation of vegetables has gone through difficulties such as water deficit, shortage of labor and high incidence of pests, especially Spodoptera eridania. Different management methods for this pest are studied to expand the existing options. Much of the management is carried out by synthetic insecticides, but there are few products registered for crops, in addition to having low efficiency. Therefore, it is of great importance to study alternatives that reduce the use of pesticides in pest management. The objective of this research was to evaluate the efficiency and selectivity of eucalyptus (Eucalyptus citriodora) oils, rosemary (Rosmarinus officinalis), sage (Salvia sclarea), sweet basil (Ocimum basilicum), citronella (Cymbopogon winterianus), neem (Azadirachta indica), ginger (Zingiber officinale), soursop (Annona muricata) and the isolated compounds eugenol and d-limonene, as an alternative management strategy for S. eridania through studies evaluating the (1) efficiency of essential oils, fixed oils and isolated compounds in the management of Spodoptera eridania; (2) compatibility of Hetorhabditis amazonensis and Steinernema rarum with essential oils, fixed and isolated compounds; (3) selectivity of essential oils, fixed and isolated compounds to Trichogramma pretiosum Riley, 1879 (Hymenoptera: Trichogrammatidae); (4) efficiency of the new nucleopolyhedrovirus isolate in the management of Spodoptera eridania. From the results obtained, it was verified that: (1) the use of essential oils, fixed and isolated compounds are promising in the management of S. eridania, with emphasis on eugenol and d-limonene compounds; (2) all tested oils reduce the efficiency of H. amazonensis and S. rarum. However, in the infectivity of the juvenile, the major compound d-limonene was considered non-toxic to H. amazonensis and S. rarum, soursop oil as nontoxic to H. amazonensis and rosemary oil as non-toxic to S. rarum, according to the classification IOBC toxicology; (3) in the action of isolated oils and compounds on the parasitism of T. pretiosum, all oils and compounds tested reduced the longevity of females, and Anagasta kuehniella eggs treated with the isolated compound eugenol and the oils of O. basilicum, E. citriodora, Z. officinale, S. sclarea, R. officinalis and C. winterianus were not parasitized by females of T. pretiosum and consequently there was no emergence of individuals in these treatments; and, (4) a new isolate of S. eridania baculovirus was identified (Spodoptera eridania nucleopolyhedrovirus Se04), presenting itself as lethal for S. eridania larvae.